Porencephalic cyst in pycnodysostosis. Issue 12 (December 1989) - Figueiredo, J; Reis, A; Vaz, R; Leáo, M; Cruz, C
Abstract : We describe a case of pycnodysostosis with porencephaly and suggest an explanation for the porencephaly by a mechanism of imbalance between brain growth and its vascular supply and a normal but unopposed cerebrospinal fluid pressure.